A Study on the L2 Stability and Transparency of Three Channel Control Architectures in Bilateral Teleoperation under Time Delays - (:unkn) unknown (My University, 2021)
Bilateral/haptic teleoperation is the remote control of a "slave" robotic system through a "master" robot or haptic interface, andinvolves the feedback of the slave interaction forces to the operator. Thus, the master operator can operate the slave as anextension of his/her body. Time delay among the robots is a long-standing problem in bilateral teleoperation. The existence offorce feedback to the operator in haptic/bilateral teleoperation makes the teleoperation system less robust to time delays on thecommunication channels. Three channel architectures have been proposed in the literature to provide increased robustnessagainst time delays with increased transparency (kinesthetic coupling). In this paper, we propose modifications on three channelarchitectures to guarantee delay independent L2 stability, while exploiting the increased transparency characteristics of thesearchitectures. The validity of the proposed approach is examined both analytically and experimentally on a bilateralteleoperation system.

İki-yönlü/haptik teleoperasyon; bir "takipçi" robotun bir "yönlendirici" robot, veyahut arayüz, aracılığıyla operatör tarafından_x000D_ uzaktan kumandasını ve takipçi robotun etkileşim kuvvetlerinin operatöre geri beslenmesini kapsar. Böylece operatör, takipçi_x000D_ robotu kendi uzuvlarının bir uzantısı gibi kullanabilir. Robotlar arasındaki iletişimde yaşanan gecikmeler, iki-yönlü_x000D_ teleoperasyonda bilinen en eski problemlerdendir. Operatöre kuvvet geri beslemesinin olması haptik/iki-yönlü teleoperasyon_x000D_ sistemlerinin gecikmelere karşı daha kararsız/dayanıksız olmasına sebebiyet vermektedir. Üç kanal mimarileri, literatürde,_x000D_ gecikmelere karşı daha dayanıklı ve yüksek transparanlığa (kinestetik bağa) izin veren mimariler olarak ortaya çıkmışlardır._x000D_ Bu makalede, üç kanal mimarilerinde, bu mimarilerin hem transparanlığından faydalanmayı amaçlayan hem de gecikmeden_x000D_ bağımsız L2 kararlılığını garantileyen değişiklikler yapılması önerilmektedir. Önerilen yaklaşımın geçerliliği hem analitik hem_x000D_ de deneysel yöntemlerle bir iki-yönlü teleoperasyon sisteminde incelenmiş, ve doğrulanmıştır.
Zaman Gecikmeleri Altında İki-Yönlü Teleoperasyonda Üç Kanallı Kontrol Mimarilerinin L2 Kararlılığı ve Şeffaflığı Üzerine Bir Çalışma